Mission-oriented capability evaluation for combat network based on operation loops - Yang Wang; Junyong Tao; Xiaoke Zhang; Guanghan Bai; Yunan Zhang (Defence Technology)
With continuous growth in scale, topology complexity, mission phases, and mission diversity, challenges have been placed for efficient capability evaluation of modern combat systems. Aiming at the problems of insufficient mission consideration and single evaluation dimension in the existing evaluation approaches, this study proposes a mission-oriented capability evaluation method for combat systems based on operation loop. Firstly, a combat network model is given that takes into account the capability properties of combat nodes. Then, based on the transition matrix between combat nodes, an efficient algorithm for operation loop identification is proposed based on the Breadth-First Search. Given the mission-capability satisfaction of nodes, the effectiveness evaluation indexes for operation loops and combat network are proposed, followed by node importance measure. Through a case study of the combat scenario involving space-based support against surface ships under different strategies, the effectiveness of the proposed method is verified. The results indicated that the ROI-priority attack method has a notable impact on reducing the overall efficiency of the network, whereas the O-L betweenness-priority attack is more effective in obstructing the successful execution of enemy attack missions.